Trends in public health policy designs for the COVID-19 pandemic in Latin America - Paz-Noguera, Bayron Alberto (Universidad y Salud, 2020)
Introduction: The Latin American countries had to design public health policies to confront the imminent arrival of the COVID-19 pandemic. Objective: To determine the trends in the designs of public health policies facing the COVID-19 pandemic in Latin America. Materials and methods: An analytical and methodological approach was applied to reconstruct the characteristics of the social problem and the designs of public policies in ten Latin American countries, using data from secondary sources. Results: The COVID-19 pandemic triggered social problems in Latin America that were caused by the unpreparedness of the countries’ health systems and their inability to contain it. Thus, countries designed social protection policies that can be outlined within three main approaches: (i) strong and strict (Argentina, Bolivia, Colombia, Ecuador, Paraguay and Peru); (ii) flexible (Chile and Uruguay) and (iii) lax (Brazil and Mexico). Conclusions: The trends in the designs of public health policies are divergent, which will affect the intensity and length of the pandemic in each country.